Sistem Pakar Penyakit Ginjal Berbasis Web - Muhammad Ariq Hendry; M. Ikhsan Gumanof; Farhan Rinsky Mulya; Dwiny Meidelfi (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
We all know that Health is important and expensive, to maintain the health of our bodies we need to take care of the organ in our body one of them is the kidney. The kidneys function to filter and remove toxins in the blood. There are still many people who don't care about their kidney health because most people do not have any symptoms until kidney disease enters an advanced stage. The medical world is increasingly using computers to assist diagnosis for prevention and treatment of a disease. One of them is the utilization of an expert system. This study aims to create an expert system that will be used to independently diagnose kidney disease without having to go to the hospital. and also aims to avoid contact with others during a pandemic.